Best Practice Guidelines and Essential Methodological Steps to Conduct Rigorous and Systematic Meta‐Reviews. Issue 3 (9th July 2019) - Hennessy, Emily A.; Johnson, Blair T.; Keenan, Ciara
Abstract : Background: A growing body of primary study and systematic review literature evaluates interventions and phenomena in applied and health psychology. Reviews of reviews (i.e., meta‐reviews) systematically synthesise and utilise this vast and often overwhelming literature; yet, currently there are few practical guidelines for meta‐review authors to follow. Objective: The aim of this article is to provide an overview of the best practice guidelines for all research synthesis and to detail additional specific considerations and methodological details for the best practice of conducting a rigorous meta‐review. Methods: This article provides readers with six systematic and practical steps along with accompanying examples to address with rigor the unique challenges that arise when authors familiar with systematic review methods begin a meta‐review: (a) detailing a clear scope, (b) identifying synthesis literature through strategic searches, (c) considering datedness of the literature, (d) addressing overlap among included reviews, (e) choosing and applying review quality tools, and (f) appropriate options for handling the synthesis and reporting of the vast amount of data collected in a meta‐review. Conclusions: We have curated best practice recommendations and practical tips for conducting a meta‐review. We anticipate that assessments of meta‐review quality will ultimately formalise best‐method guidelines.